Politeness Principles in Jeffrey Dahmer’s Netflix Documentary: A Pragmatics Study - Firdaus, Ghaida; Zuraida, Ida (Universitas Galuh, 2024)
The goal of the study was to examine the types and functions of the politeness principles in Jeffrey Dahmer’s Netflix documentary. The qualitative descriptive approach using Creswell’s theory was employed in this study (2009). This analysis used the ideas of the theory of politeness from (Leech, 2014) to the data. This study set out to determine the types of politeness rules and how they are used in various contexts. According to the study’s findings, there are twenty examples of politeness principles in Jeffrey Dahmer’s Netflix documentary. These examples include the following: twelve data of tact (60%); three data of generosity (15%); one data of approbation (5%); one data of modesty (5%); two data of agreement (10%); and one data of sympathy (5%). Based on the analysis, the function of each politeness principles used in Jeffrey Dahmer’s Netflix Documentary is different according to each type of politeness principle used. Out of 4 data, there are only 3 data found in Jeffrey Dahmer’s Netflix Documentary. Convivial with 13 data (65%), competitive with 4 data (20%), collaborative with 3 data (15%). Convivial is the most dominant used in this research, it is being performed by the speaker to aims in compliance with the social purposes. Competitive is in the second position because this function is to outperform social goals. Collaborative is the third that appears because it is disregard societal goals